Regionalizing Infrastructure for Deepening Market Integration : The Case of East Africa - Kessides, Ioannis N.; Benjamin, Nancy C. (World Bank, Washington, DC, 2014)
The East African Community has long recognized that regional economic integration can yield significant welfare gains to its member states. To that end, the community has been making steady progress towards the removal of tariffs and quantitative restrictions to trade. Moreover, in recent years, there has been an increasing recognition that: (a) even greater welfare gains could be realized through deeper forms of regional integration which entail harmonization of legal, regulatory and institutional frameworks; and (b) reforms that reduce cross-border transaction costs and improve the performance of "backbone" infrastructure services are arguably even more important for the creation of an open, unified regional economic space than trade policy reforms narrowly defined. Disparities of regulatory treatment across borders can introduce distortions that hinder both cross-border trade and the aggregate flows of investment on a regional basis. Regulatory harmonization and infrastructure regionalization could make a significant contribution to the region's economic development by promoting a more efficient utilization of its human and physical resources, enhancing connectivity, reducing the costs of trade, and facilitating the integration of the continent with the global economy.